How tax audit and tax advisory can benefit from big data analytics tools data analysis and processing in relational databases using SQL Server and Power Pivot & Power View in Excel - Santos, M.; Laureano, Raul M. S.; Carlos E. R. Albino (2018 13th Iberian Conference on Information Systems and Technologies (CISTI), 2018)
In the context of business analytics, the tax consultants and auditors face challenges when conducting data analysis for tax optimization based on big commercial databases extracted from the management systems of organizations. This article focuses on big data analytics by using Business Intelligence (BI) tools provided by Microsoft. In this paper, we combine the storage and pre-processing capacity of SQL Server (Developer edition) with the analysing and reporting add-ins supported by Excel (Power Pivot and Power View). Both BI solutions were applied on accounting and tax data extracted from a ERP system in order to demonstrate how tax professionals can conduct big data analysis to maximize value added tax recovery.